On Artinianness of Formal Local Cohomology, Colocalization and Coassociated Primes - Eghbali, Majid (Mathematica Scandinavica, 2013)
This paper at first concerns some criteria on Artinianness and vanishing of formal local cohomology modules. Then we consider the cosupport and the set of coassociated primes of these modules more precisely.